Flexible Working Arrangements and Supervisor Trust on Work-Life Balance Mediated by Perceived Organizational Support - Hendry; Debora Tambunan; Emma Novirsari; Maduma Sari Sagala; Muhammad Fathoni (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Lecturers in higher education face challenges in balancing professional and personal responsibilities, necessitating flexible work policies and supportive leadership to enhance well-being. This study aims to examine the influence of Flexible Working Arrangement and Supervisor Trustworthiness on Work-Life Balance, with Perceived Organizational Support as a mediator, among tenured lecturers at Universitas Prima Indonesia. A quantitative approach was employed, utilizing a structured questionnaire with a 5-point Likert scale to collect data from 129 tenured lecturers, representing a 92% response rate from the total population of 140. Data were analyzed using Partial Least Squares Structural Equation Modeling to test direct and mediated relationships. The findings reveal that Flexible Working Arrangement and Supervisor Trustworthiness significantly enhance Perceived Organizational Support, which in turn positively affects Work-Life Balance. Additionally, Perceived Organizational Support mediates the relationship between both Flexible Working Arrangement and Supervisor Trustworthiness and Work-Life Balance. These results highlight the critical role of flexible policies and trustworthy leadership in fostering lecturers’ well-being in the Indonesian academic context, where such studies are limited. The study suggests that universities implement flexible schedules and leadership training to promote Work-Life Balance, contributing to improved job satisfaction and institutional productivity.